Comparison of the Effects of Help-Seeking Training and Self-Compassion Training on Social Competence, Achievement Motivation, and Academic Resilience - Shafiei Sani, Shokofeh; Mahoor, Hosein; Yamini, Mohammad (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of the present study was to compare the effects of help-seeking training and self-compassion training on students’ social competence, achievement motivation, and academic resilience. Methods and Materials: The present study employed a quasi-experimental design with a pretest-posttest and follow-up, along with a control group. The statistical population of this study included all female high school students in Sabzevar during the 2021-2022 academic year (350 individuals). The sample consisted of 45 students selected through purposive sampling and randomly assigned to three groups: help-seeking training (n=15), self-compassion training (n=15), and control group (n=15). Data were collected using the Social Competence Questionnaire (Felner, 1990), Achievement Motivation Questionnaire (Hermans, 1970), and Academic Resilience Questionnaire (Martin & Marsh, 2008). The help-seeking sessions followed the Nelson-Lee Gall model (1981) and were conducted in 10 weekly 90-minute sessions. The self-compassion training sessions were based on Gilbert’s model (2009) and also conducted in 10 weekly 90-minute sessions. Data analysis was performed using repeated measures ANOVA and SPSS-26 software. Findings: Results indicated that both help-seeking training and self-compassion training were effective in improving social competence, achievement motivation, and academic resilience (P<0.01). Additionally, these results showed that self-compassion training was more effective than help-seeking training in enhancing social competence, achievement motivation, and academic resilience (P<0.01). Conclusion: It can be concluded that help-seeking training and self-compassion training are effective in improving social competence, achievement motivation, and academic resilience.